Synthesis and antituberculosis activity of new N-phenyl-N '-[4-(5-alkyl/arylamino-1,3,4-thiadiazole-2-yl)phenyl]thioureas - (:unkn) unknown (ELSEVIER SCIENCE SA, 2002)
In this study, eight original N-phenyl-N'-[4-(5-alkyl/arylamino-1,3,4-thiadiazole-2-yl)phenyl]thiourea, derivatives were synthesized and tested for antituberculosis activity. Antituberculosis activities of the synthesized compounds were screened in vitro using BACTEC 460 Radiometric System against Mycobacterium tuberculosis H37Rv at 6.25 mug/ml. The highest inhibition observed with the synthesized compounds is 67% for N-phenyl-N'-[4-(5-cyclohexylamino-1,3,4-thiadiazole-2-yl)phenyl]thiourea. (C) 2002 Editions scientifiques et medicales Elsevier SAS. All rights reserved.
Keywords: 1,3,4-thiadiazole; thiourea; antituberculosis activity